The Effect of Conflict and Job Stress on Showroom Employee Performance at PT Tunas Mobilindo Perkasa Karawang Area - Hidayat, Topik; Mohammad Darul Fadli, Uus; Ery , Rosmawati (Research in Management of Technology and Business, 2024)
In the current era of globalization, the automotive industry has become one of the fastest-growing, modern, and innovative sectors. The ever-increasing public demand for both two-wheeled and four-wheeled vehicles encourages this industry to improve its products’ quality continuously. In this context, workplace conflict and stress can impact employee productivity in the automotive industry. Therefore, this study explores the relationship between workplace conflict, stress, and employee performance. This study used a quantitative descriptive approach conducted at PT Tunas Mobilindo Karawang Area. The population in this study consisted of 78 employees. The sampling technique used was non-probability sampling, with a sample size of 76 respondents, which was determined using the Slovin formula with an error rate of 2%. Data was collected by sending questionnaires via Google Forms. Data analysis was conducted using Structural Equation Modeling (SEM), with the Partial Least Square (PLS) method using the SmartPLS version 4 application. The results showed that conflict positively influences employee performance, while job stress has a positive and significant influence.